2021
DOI: 10.47803/rjc.2021.31.3.573
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Innate Immune Response to Myocardial Infarction in a Highly Efficient Experimental Animal Model

Abstract: The reduction in mortality following acute myocardial infarction (AMI) is an important achievement of modern medicine. Despite this progress, AMI remains the most common cause of heart failure (HF) and HF-related morbidity and mortality. The involvement of the innate immune response in different stages after AMI has at tracted important attention in recent years. With the increasing range of potential therapeutic compounds and delivery vectors, the need of highly efficient experimental AMI models is increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Wild-type (C57BL/6) female mice, 8–12 weeks of age, 20–25 g body weight, underwent permanent left anterior descending (LAD) coronary artery ligation as previously described [ 20 , 21 ]. All animals were allowed to acclimatize for at least one week before being included in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild-type (C57BL/6) female mice, 8–12 weeks of age, 20–25 g body weight, underwent permanent left anterior descending (LAD) coronary artery ligation as previously described [ 20 , 21 ]. All animals were allowed to acclimatize for at least one week before being included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Mouse models of MI are essential in cardiovascular research, to assess the effects of potential treatments on cardiac function, immune cell infiltration and MI size [ 20 ]. We have previously shown that short-term S100A8/A9 blockade by ABR-238901 favorably tips the immune inflammation/repair balance in the infarcted heart and improves cardiac function long-term.…”
Section: Introductionmentioning
confidence: 99%